High-performance organosilicon–refractory bauxite: Coating and fundamental properties. (20th May 2019) - Ma, Ming; Chen, Qian; Wang, Chaohui; Fu, Hao; Li, Tianyu
Highlights: The method of coating refractory bauxite in an organosilicon solvent. The surface coating effects of different organosilicon solvents on high-alumina refractory bauxite. The fundamental properties of different organosilicon–refractory bauxite materials. The comprehensive performance evaluation of organosilicon–refractory bauxite based on the grey target decision-making method. Abstract: The aim of this study is to improve the fundamental properties of refractory bauxite to promote its further application in the heat-resistant asphalt pavement technology. A method of coating refractory bauxite in an organosilicon solvent is proposed. The surface coating effects of different organosilicon solvents on high-alumina refractory bauxite are compared and evaluated using the macropore structure and the microsurface morphology. Based on the optimal treatment process and material proportion, the fundamental properties of different organosilicon–refractory bauxite materials are analyzed systematically. Based on the grey target decision-making method, the comprehensive performance of different organosilicon–refractory bauxite is evaluated. On this basis, the organosilicon–refractory bauxite material with better comprehensive performance was added into the asphalt mixture and its pavement performances were identified. The results show that a large number of pores of refractory bauxite are sealed by using organosilicon solvents. Moreover, the coating effect is good. In addition, the heat resistance is improved. The mechanical property and adhesion of refractory bauxite are increased by 30.66% and 66.67%, respectively.